2013
DOI: 10.1523/jneurosci.2090-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Spine Formation by ErbB4 in PV-Positive Interneurons

Abstract: The trophic factor neuregulin 1 (Nrg1) and its receptor ErbB4 are schizophrenia candidate genes. NRG1-ErbB4 signaling was thought to regulate spine formation and function in a cell-autonomous manner. Yet, recent studies indicate that ErbB4 expression is largely restricted to GABAergic interneurons and is very low or absent in pyramidal cells. Here, we generated and characterized cell type-specific ErbB4 mutant and transgenic mice. Spine density and the number of excitatory synapses were unaltered by neither de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 50 publications
5
44
1
1
Order By: Relevance
“…Therefore, we propose that NRG1 regulates EAAC1 by the direct activation of ErbB4 receptors. Altered NRG1-ErbB4 signaling is shown to contribute to NMDA hypofunction in schizophrenia (45)(46)(47). Based on the previous findings above, our findings support the notion that up-regulation of EAAC1 by NRG1 may provide a potential mechanism of glutamatergic hypofunction in schizophrenia.…”
Section: Neuregulin 1 Regulates Eaac1supporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, we propose that NRG1 regulates EAAC1 by the direct activation of ErbB4 receptors. Altered NRG1-ErbB4 signaling is shown to contribute to NMDA hypofunction in schizophrenia (45)(46)(47). Based on the previous findings above, our findings support the notion that up-regulation of EAAC1 by NRG1 may provide a potential mechanism of glutamatergic hypofunction in schizophrenia.…”
Section: Neuregulin 1 Regulates Eaac1supporting
confidence: 88%
“…These results suggest that EAAC1 expression remained decreased in the remain- ing PV clusters, which decreased in PV-ErbB4 Ϫ/Ϫ mice. However, a recent study has revealed that the spine density and the number of excitatory synapse are reduced in PV-ErbB4 Ϫ/Ϫ mice (47), which may contribute to the reduction in EAAC1 expression in the mouse model. Therefore, further study is required to determine whether it is a direct effect or whether it is an effect caused by the changes of synapse in PV-ErbB4 Ϫ/Ϫ mice.…”
Section: Neuregulin 1 Regulates Eaac1mentioning
confidence: 98%
“…In ErbB4 mutant mice, the number of excitatory synapses is decreased, and amplitude and frequency of miniature excitatory postsynaptic potential (mEPSP) are also reduced, in PV ? GABAergic neurons, indicating synaptic dysfunction [42,43]. In situ hybridization studies in rodent and monkey models have shown that the mRNA expression pattern is consistent with the location of GABAergic neural cells [44].…”
Section: Discussionmentioning
confidence: 80%
“…As discussed above, Erbb4 expression in the brain is restricted to interneurons in adult animals (Fazzari et al, 2010; Vullhorst et al, 2009). Besides, deletion of Erbb4 in pyramidal neurons of floxed Erbb4 mice (by retroviral Cre) or by CaMKII-Cre did not alter the density of dendritic spines or mEPSC (Fazzari et al, 2010; Yin et al, 2013b) and Erbb4 knockdown in cultured hippocampal neurons had no effect on Nrg1 induction of spines (Cahill et al, 2013). Spine reduction in mice where Erbb4 was knocked out by hGFAP-Cre or in hippocamapal slices by lentivirus may be due to a homeostatic mechanism to compensate hyperactivity of pyramidal neurons (because of hypofunction of GABAergic circuitry) (see below).…”
Section: Assembly Of Neuronal Circuitrymentioning
confidence: 97%